Refugee - Gratz, Alan, 1972- (2017)
Although separated by continents and decades, Josef, a Jewish boy living in 1930s Nazi Germany; Isabel, a Cuban girl trying to escape the riots and unrest plaguing her country in 1994; and Mahmoud, a Syrian boy in 2015 whose homeland is torn apart by violence and destruction, embark on harrowing journeys in search of refuge, discovering shocking connections that tie their stories together
10-13
Accelerated Reader
Accelerated Reader AR
Keywords: Jewish refugees -- Juvenile fiction; Jewish refugees -- Juvenile fiction; Refugees -- Cuba -- Juvenile fiction; Refugees -- Syria -- Juvenile fiction; Refugees -- Juvenile fiction; Emigration and immigration -- Juvenile fiction; Survival -- Juvenile fiction; Historical fiction; Fiction; Historical fiction; Juvenile works; Historical fiction; Historical fiction